ANALISIS KINERJA PENERIMAAN RETRIBUSI PASAR DI KABUPATEN SLEMAN TAHUN 2006 – 2010 - Octaviana Candra Dewi; Nugroho SBM (Diponegoro Journal of Economics, 2014)
ABSTRACT Market’s tax is one of the kinds of important source of revenue for the district of Sleman area. This was proven during the 2006-20010 fiscal year; the acceptance of market’s tax was increased. However, in 2006 the tax reception did not reach the target, which was equal to -6.39%. This case indicates that there were some problems in the performance of the market’s tax acceptance in Sleman. The purpose of this study is to analyze the effectiveness of market’s acceptance tax, to analyze the performance of the markets’ acceptance tax, to analyze the potential of the market’s tax and to formulate some appropriate strategies to improve the performance of the market’s acceptance tax in Sleman. The data used in this study were secondary data and primary data. The sampling method used in this study was purposive sampling which includes sellers, officers, market’s tax collector, and employee of Sleman Market Service, with total 51 respondents. Based on the calculation of the effectiveness level in 2006-2010, the writer found that the average of the market’s tax acceptance in Sleman was not effective, that was equal to 29,45%.Based on the SWOT analysis, it was known that SKPD’s Sleman Market Service was in quadrant I in the SWOT diagram, which was located in growth quadrant with numbers were above of the average. It was also known to the vertical axis (business opportunities) of 2.79, and the horizontal axis (strength) of 2.44. This case indicates that the strength of Sleman Market Service is much greater than its disadvantages and the business opportunities that exist are higher than the threat of the business itself. Thereby, the right strategy that should be conducted by the Officers of Sleman Market Service is an aggressive strategy, the strategy that utilizes the existing strengths to achieve the opportunities that available.